Penguatan Daya Saing UMKM Kampung Lontong Menggunakan Strategi SWOT dan Matrik IE - Muqarrobi, Muhammad Ferdi; Hamsa, Akhmad Fadhilah; Choirunnisa, Nadia (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia’s economy. One example is Kampung Lontong in Surabaya, known as a center for traditional rice cake (lontong) production. However, the area faces several challenges, including limited digital marketing, inefficient traditional production methods, and unstable raw material supply. This study uses a qualitative descriptive approach through field observations and interviews with business owners, combined with SWOT analysis and the Internal-External (IE) matrix. The analysis reveals that Kampung Lontong’s strengths lie in its product quality, production capacity, and strategic location. Opportunities arise from strong market demand and the growth of culinary tourism. A Strength–Opportunity (SO) strategy is recommended to capitalize on these advantages. According to the IE matrix, Kampung Lontong is positioned in Quadrant V (Hold and Maintain), indicating the need to stabilize operations while gradually improving production efficiency and digital marketing efforts. This strategy aims to ensure sustainable growth while preserving the traditional identity that makes Kampung Lontong unique and attractive to both local and visiting consumers.